2014
DOI: 10.1002/ange.201409454
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature N2 Binding to Two‐Coordinate L2Fe0 Enables Reductive Trapping of L2FeN2 and NH3 Generation

Abstract: The 2-coordinate (CAAC) 2 Fe complex [CAAC = cyclic (alkyl)(amino)carbene] binds dinitrogen at low temperature (T < −80 °C). The resulting putative 3-coordinate N 2 -complex, (CAAC) 2 Fe(N 2 ), was trapped by one electron reduction to its corresponding anion [(CAAC) 2 FeN 2 ] − at low temperature. This complex was structurally characterized and features an activated dinitrogen unit that can be silylated at the β-nitrogen. KeywordsIron; Nitrogen fixation; Low-coordinate; Carbenes While hundreds of transition-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 56 publications
1
52
0
2
Order By: Relevance
“…Ung et al reported a low-coordinate Fe-CAAC system (CAAC = cyclic(alkyl)(amino)carbene) that, when reduced with KC 8 in the presence of 18-crown-6, forms (CAAC) 2 Fe(μ-N 2 )K(18-crown-6) ( 17 ) [74]. In contrast to other examples where addition of a crown ether results in sequestration of the coordinated cation, end-on K + still forms a contact ion pair with the anionic Fe-N 2 complex even when chelated by 18-crown-6, similar to the Mo complex 3 .…”
Section: Effects Of Alkali Cations On N2 Activation By Transition mentioning
confidence: 99%
See 1 more Smart Citation
“…Ung et al reported a low-coordinate Fe-CAAC system (CAAC = cyclic(alkyl)(amino)carbene) that, when reduced with KC 8 in the presence of 18-crown-6, forms (CAAC) 2 Fe(μ-N 2 )K(18-crown-6) ( 17 ) [74]. In contrast to other examples where addition of a crown ether results in sequestration of the coordinated cation, end-on K + still forms a contact ion pair with the anionic Fe-N 2 complex even when chelated by 18-crown-6, similar to the Mo complex 3 .…”
Section: Effects Of Alkali Cations On N2 Activation By Transition mentioning
confidence: 99%
“…The third system capable of catalytic reduction of N 2 to NH 3 has been explored by the Peters group, utilizing Fe tris(phosphino)borane and -alkyl complexes ( 15 , 16 ), which can produce up to 64 equiv NH 3 per Fe depending on the catalyst [73, 97, 98]. The Peters group also recently reported an Fe-CAAC system ( 17 ) that can catalytically reduce N 2 to generate up to 3.4 equiv NH 3 [74]. …”
Section: Do Alkali Cations Play a Role In The Catalytic Reduction mentioning
confidence: 99%
“…In 2003, Yandulov and Schrock29303132 reported the first successful example of the catalytic conversion of dinitrogen gas into ammonia using a molybdenum–dinitrogen complex as a catalyst and in 2013 Peters and co-workers33343536373839 reported the iron-catalysed transformation using an iron–dinitrogen complex as a catalyst. We also found that several dinitrogen-bridged dimolybdenum complexes such as [{Mo(N 2 ) 2 (PNP)} 2 (μ-N 2 )] ( 2 ; PNP=2,6-bis(di- tert -butylphosphinomethyl)pyridine)404142 and molybdenum–nitride complexes bearing PNP-type pincer ligands43 or mer -tridentate triphosphine44 worked as more effective catalysts towards ammonia formation under ambient reaction conditions, where up to 63 equiv.…”
mentioning
confidence: 99%
“…The imido-hydride and di-hydrideamido Mo IV complexes have been isolated and characterized. [2] Most impressively,s everal Mo, [3] Fe, [4] and Co [5] complexes have proven efficient catalysts for NH 3 and N(SiMe 3 ) 3 synthesis,with TON (turn over number) up to circa 415 and 220, respectively. N 2 functionalization using homogeneous metal complexes under mild conditions is one of the most challenging problems facing chemists.…”
Section: In the Memory Of Pascal Le Flochmentioning
confidence: 99%
“…

Intermolecular,s tepwise functionalization by BH bonds of a( triphosphine)Mo IV -nitrido complex generated by N 2 splitting is reported. [2] Most impressively,s everal Mo, [3] Fe, [4] and Co [5] complexes have proven efficient catalysts for NH 3 and N(SiMe 3 ) 3 synthesis,with TON (turn over number) up to circa 415 and 220, respectively. Addition of PinBH to the [Mo(H) 2 (N(BPin) 2 )] + complex at room temperature results in the liberation of borylamines from the metal center.

N 2 functionalization using homogeneous metal complexes under mild conditions is one of the most challenging problems facing chemists.

…”
mentioning
confidence: 99%